AGILE LEADERSHIP UNVEILED: ESSENTIAL TRAITS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The expectation on becoming agile is rising. Businesses implement agile values in the last 20 years, especially in the software and product development, and in the fast-changing and often unforeseen environment, agility may sound as a solution to fast adaptation and flexibil-ity. At the hard of this adaptability lies the agile leader, driving the organizational resilience and innovation. While micro and macro levels of corporate hierarchy have been widely studied, meso level and hierarchical interplay between individual and leader are so far being neglected. The aim of this study is to spot key attributes that define agile leadership excellence. To achieve this aim, a qualitative study based on interviews has been performed. In total, 40 Chief Technology Officers (CTO) who apply agile values and methods in their daily businesses have been interviewed during July-August 2024. In addition, a systematic literature review and bibliometric analysis have been applied to elaborate on academic research in this field. The bibliometric analysis is based on a literature review of publications obtained from Scopus using an inclusive search strate-gy. To visualize the data, Bibliometrix and VOSviewer have been used. This article aims to enhance research on agile leadership by identifying key traits of agile leader to manage complexity, reciprocate team capabili-ties and enhance outcome. By examining these traits, author is uncovering the role of leader regarding all stakeholders. The study comes with the conclusion and recommendations for both business and academia.